Heuristic method for restoring service in electrical power distribution systems (2006)
When a fault occurs in a radial topology electrical power distribution system, the isolation of the section where the fault occurred causes the isolation of some portions of the feeder downstream of the failed area, therefore, the next step must be to restore the service to the affected users. Such restoration should be done as quickly as possible, taking into account restrictions of system topology and feeder capacity. This article presents a heuristic method that allows the restoration of the service through the reconfiguration of feeders. The results are presented for a distribution system of 11 bars and three main feeders.